2005
DOI: 10.1038/modpathol.3800403
|View full text |Cite
|
Sign up to set email alerts
|

Endocervical adenocarcinomas associated with lobular endocervical glandular hyperplasia: a report of four cases with histochemical and immunohistochemical analyses

Abstract: We report on four cases of endocervical adenocarcinoma associated with lobular endocervical glandular hyperplasia using histochemical and immunohistochemical analyses. The patients ranged in age from 59 to 67 years (mean 62 years). Chief complaints were watery vaginal discharge in two cases, genital bleeding in one and no subjective symptoms in one. Cytological examinations of the cervical smears revealed adenocarcinoma cells and benign-looking glandular cells with intracytoplasmic golden-yellow mucin in all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 55 publications
3
34
1
Order By: Relevance
“…To avoid misdiagnosis, it must be kept in mind that LEGH is sometimes mixed with malignant cervical lesions; several previous studies have reported some LEGH cases mixed with MDA, 7,11 and we reported previously four LEGH cases coexisting with adenocarcinoma. 18 It has been well demonstrated that an INCI is an invagination of the cytoplasm into the nucleus; however, the underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid misdiagnosis, it must be kept in mind that LEGH is sometimes mixed with malignant cervical lesions; several previous studies have reported some LEGH cases mixed with MDA, 7,11 and we reported previously four LEGH cases coexisting with adenocarcinoma. 18 It has been well demonstrated that an INCI is an invagination of the cytoplasm into the nucleus; however, the underlying mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported four cases of endocervical adenocarcinoma associated with LEGH. 18 We included 10 control cases each of normal endocervical glandular lesions and common mucinous AC of the cervix. All patients underwent a hysterectomy and gave written, informed consent.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…LEGH in the uterine cervix is thought to be a precursor lesion of gastric-type cervical adenocarcinoma [5], which is often identified in patients with PJS. Therefore, the premalignant potential of an ovarian mucinous tumor resembling LEGH should be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a differential diagnosis between LEGH and MDA is challenging. Although LEGH was first reported as a benign disease, it has been reported as a precursor of MDA, because of frequent association between LEGH and MDA as well as its genetic characteristics 6, 7, 8, 9, 10, 11. We previously reported that some LEGH lesions were a precancerous form of MDA due to the pattern of X chromosome inactivation using the human androgen receptor (HUMARA) method 12.…”
Section: Introductionmentioning
confidence: 99%